2010
DOI: 10.1159/000327506
|View full text |Cite
|
Sign up to set email alerts
|

Splenomegaly in Primary Antiphospholipid Syndrome without Accompanying Portal Hypertension or Comorbidity

Abstract: Objective: To demonstrate the presence of splenomegaly in primary antiphospholipid syndrome (PAPS) patients without accompanying portal hypertension or comorbidity. Methods: Twelve patients (7 women) aged 23–65 years followed upon the diagnosis of PAPS were enrolled in the study. We documented the identified causes of splenomegaly in patients with PAPS, and searched for the potential causes of splenomegaly in patients with spleen enlargement. PAPS patients with or without splenomegaly were evaluated in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…The pathogenesis of thrombocytopenia in antiphospholipid antibody-positive patients is not fully understood. However, based on currently available data [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ], we here summarize four different mechanisms, reported in Table 2 .…”
Section: Aps and Thrombocytopeniamentioning
confidence: 99%
“…The pathogenesis of thrombocytopenia in antiphospholipid antibody-positive patients is not fully understood. However, based on currently available data [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ], we here summarize four different mechanisms, reported in Table 2 .…”
Section: Aps and Thrombocytopeniamentioning
confidence: 99%
“…In patients with APS, splenomegaly that develops after splenic or portal vein thrombosis may result in mild thrombocytopenia. Although splenomegaly is accepted as an unexpected finding in patients with APS, a recent study showed that splenomegaly can be found in patients with APS with no portal hypertension, infection, hematological disorders, or malignancy [82].…”
Section: Increased Platelet Poolingmentioning
confidence: 99%
“…Several studies have reported that ascites is a relatively common AE of RAM treatment 17,18,30,31 . Splenomegaly and portal hypertension are closely related 32 . The VEGFR‐2 signaling pathway is dependent on portal hypertensive syndromes, such as development of a hyperdynamic splanchnic circulatory state and formation of portal‐systemic collateral vessels 33 .…”
Section: Discussionmentioning
confidence: 99%
“…17,18,30,31 Splenomegaly and portal hypertension are closely related. 32 The VEGFR-2 signaling pathway is dependent on portal hypertensive syndromes, such as development of a hyperdynamic splanchnic circulatory state and formation of portal-systemic collateral vessels. 33 Previous reports have revealed that decreased portal venous inflow and increased splanchnic arteriolar resistance were observed by inhibiting VEGFR-2 significantly.…”
Section: Assessment Of Aes In Ram Treatmentmentioning
confidence: 99%